Process development for goat milk shrikhand added with kiwi fruit - Pathrikar, A D; Patange, D D; Mote, G V; Udachan, I S; Lokhande, S M (Journal of Postharvest Technology, 2021)
This study was undertaken with the objectives of to develop nutritious goat milk shrikhand added with kiwi fruit pulp. Having the multifarious properties  of goat milk and kiwi fruit. Chakka was prepared through goat milk with culture addition. The level of sugar and kiwi fruit pulp in goat milk chakka was  optimized through RSM with 13 different samples. The best combination of shrikhand containing 6.85% kiwi fruit pulp and 40% sugar was selected on  based on sensory analysis (9 point hedonic)i.e. sensory evaluation score was 8.00, 7.83, 7.91, 7.82, 7.87 for colour, sweetness, taste & flavour, texture  & consistency and overall acceptability. The selected concentration was evaluated for sensory, Physico-chemical analysis. Kiwifruit is rich in vitamin C  with good source of other nutrients such as folate protein, carbohydrate, potassium, and dietary fibre which is good for health and goat milk contains  good amount of fat, protein, lactose and vitamins.
Keywords: Shrikhand; Kiwi; health benefits; goat milk; response surface methodology